Constructing The Understanding of Non-Positivist Research Paradigm and Method - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2022)
Purpose—This research aims to build an understanding of non-positivist research paradigms and methods. The development of problems in society, especially those related to social problems, is increasingly complex. Design/methodology/approach - This research used an interpretive paradigm approach. The interpretive approach departs from efforts to seek explanations of social or cultural events based on the perspectives and experiences of the people being studied. Findings - The result of this research showed that the six paradigms that have been described, namely 1) Interpretive, 2) Phenomenology, 3) Symbolic Interactionism, 4) Critic, 5) Postmodernist, and 6) Spiritualist, have differences in their respective advantages and disadvantages. Practical implications - The focus of each existing paradigm is also different, so researchers must be careful when using it. Differences can start from how to focus the research theme to be explored to how the report pattern should be made. Thus, these developments may lead researchers to solve increasingly complex problems and find the root of the problem.